Ultrafine N-doped carbon nanoparticles with controllable size to enhance electrocatalytic activity for oxygen reduction reaction. Issue 112 (22nd November 2016) - Wang, Wenxi; Shi, Yang; Li, Minchan; Wang, Zhenyu; Wu, Shaofei; Lyu, Fucong; Shang, Chaoqun; Lu, Zhouguang
Abstract : The ORR electrocatalytic activity of ultrafine nanoparticles prepared from carbonization of Sterculia scaphigera is significantly improved through a simple hydrothermal treatment. Abstract : There are several drawbacks to the current oxygen reduction reaction (ORR) involving the kinetically sluggish process and expensive catalysts which impede the mass production of noble-metal materials for application in clean and efficient energy conversion devices. Herein, a type of ultrafine carbon nanoparticle with high nitrogen doping concentration can be simply prepared from a conveniently available precursor through a green and cost-effective hydrothermal process. With the aid of water, not only is the product's specific surface area enlarged, but the pore structure is also enriched, and there is improvement in the degree of graphitization and nitrogen-doped content. Meanwhile, the size of the carbon particle can be readily tuned to a nanoscale by changing the duration of the hydrothermal reaction. Interestingly, electrocatalytic activity is dramatically enhanced with the transformation of the carbon size and nitrogen structure. The characterization reveals that we have achieved a highly satisfactory electrocatalytic activity for ORR, a relatively positive onset potential of −0.02 V ( vs. Hg/HgO) in alkaline media and 0.55 V ( vs. Ag/AgCl) in acidic media, a higher diffusion-limiting current density than that of Pt/C, as well as outstanding stability and superior tolerance durability to methanol. Both the simplicity of the operation and the employed biomass precursor exactly meet the criteria for significant cost-saving, easy scale-up and eco-friendly demands for energy storage.